First record of a cold-seep squat lobster Munidopsis lauensis Baba and de Saint Laurent, 1992 (Anomura: Galatheoidea) from Indian waters - Maria-Judith Gonsalves; Shivam Tiwari; Vinay P. Padate; V. Deepak Samuel; Jigneshkumar Trivedi (Nauplius)
Abstract The present study reports the first zoogeographical record of the squat lobster Munidopsis lauensis Baba and de Saint Laurent, 1992 from a cold-seep site in the Krishna-Godavari Basin (Bay of Bengal), Northern Indian Ocean. Molecular analysis of the partial mitochondrial gene coding for cytochrome C oxidase subunit I (COI mtDNA), and mitochondrial 16S ribosomal RNA (16S rRNA) validated its identity. The present observation extends its geographical distribution to the Northern Indian Ocean. Additionally, molecular barcodes (COI) were generated for Munidopsis scobina Alcock, 1894, Munidopsis wardeni Anderson, 1896, and Shinkaia crosnieri Baba and Williams, 1998 collected from the Indian Exclusive Economic Zone.